PSYCHOLOGICAL WELL-BEING DAN RESILIENSI MASYARAKAT SAAT PANDEMI COVID-19 - Friska Tiurdauli Hutagalung; Albertus Budi Arianto; Friska Sinaga (Jurnal Kesehatan, 2022)
The COVID-19 pandemic has caused various impacts, one of which is the psychological impact in the form of feelings of fear, anxiety, and worry that will result in psychological well-being. Psychological well-being is a mental condition that is healthy, positive, and functioning optimally. Resilience is an individual's ability to adapt positively in the face of a problem. The purpose of this study was to identify the relationship between psychological well-being and community resilience to the COVID-19 pandemic in West Bandung Regency. This research method uses quantitative methods with an analytical cross-sectional design. The questionnaire instrument used the WHO-5 Well-Being Index to measure psychological well-being and The Brief Resilience Scale (BRS) to measure resilience which was distributed via google form to 399 respondents. Population in West Bandung Regency as many as 909,381 people. Data were collected using two questionnaires, namely psychological well-being and resilience. Spearman rank was used to analyze the data. The results showed that there was a significant correlation between psychological well-being and resilience of 0.00 (p < 0.05). The community's suggestions are expected to maintain psychological well-being in a positive and good condition during the COVID-19 pandemic because it will have a positive impact on the community's adaptability/resilience, and vice versa.